MANAJEMEN MUTU PEMBELAJARAN DI LEMBAGA PENDIDIKAN ISLAM - Subhan, Moh. (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2013)
Islamic educational institutions is a form of organization that is held to develop social institutions, both permaen and capricious. This institution has certain patterns in the play function, as well as having its own structure that can bind individuals who are in the shade, so that these institutions have legal force of its own. Quality management is a tool that allows education professionals to adapt to the